A high-strength light-absorbing heat-generating fiber and a preparation method thereof

By mixing the modified polyamide ester with nano microcapsules and melt spinning to produce high-strength light-absorbing heating fibers, the problem of existing warm-insulating heating fibers affecting the fabric's usage performance is solved, and the comprehensive performance of high strength, excellent heat resistance and good warm-insulating effect is achieved.

CN119162694BActive Publication Date: 2025-03-28SHANGHAI AOLING TEXTILE NEW MATERIAL
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411557143.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-04
Publication Date
2025-03-28
Estimated Expiration
2044-11-04

AI Technical Summary

Technical Problem

While improving the heating performance of fabrics, existing warm heating fibers can easily affect the basic usage performance of fabrics, such as strength and heat resistance.

Method used

High-strength light-absorbing heating fibers were prepared by mixing the modified polyamide ester with nano microcapsules and melt spinning. The modified polyamide esters form hyperbranched polyamide esters by crosslinking maleic anhydride, diisopropanolamine and trimethylolpropane, and react with phenylagenic acid to enhance heat resistance and strength. Nanomicrocapsules are made by coating mesoporous melamine resin on the surface of the nanopowder, which further enhances the heat resistance and strength of the fibers.

Benefits of technology

The light-absorbing heating fiber with high strength and excellent heat resistance can not only provide good warmth in the fabric, but also do not affect the basic usage performance of the fabric.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention discloses a high-strength light-absorbing and heating fiber and a preparation method thereof, and relates to the technical field of functional fiber preparation. The high-strength light-absorbing and heating fiber prepared by the present invention is prepared by melt spinning after mixing modified polyamide ester with nano-microcapsules; the modified polyamide ester fiber is prepared by melt spinning of modified polyamide ester, and the modified polyamide ester is prepared by cross-linking maleic anhydride, diisopropanolamine and trimethylolpropane to form hyperbranched polyamide ester, and then reacting with trimesic acid, which enhances the heat resistance and strength of the modified polyamide ester, and the nano-microcapsules are prepared by coating mesoporous melamine resin on the surface of nano-powder, and the nano-powder includes far-infrared ceramic powder and nano-zirconium carbide, which further enhances the heat resistance and strength of the light-absorbing and heating fiber.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of functional fiber preparation, and in particular to a high-intensity light-absorbing and heat-generating fiber and a preparation method thereof. Background Art

[0002] With the development of economy and the improvement of living standards, people's requirements for wearing comfort are constantly rising. Simple functional fabrics can no longer meet the requirements, which puts higher requirements on the research and development of new products. Polyamide ester fiber is a chemical fiber spun from a polymer made by copolymerization of terephthalic acid, ethylene glycol and caprolactam. Polyamide ester fiber has relatively good cotton-like characteristics in terms of strength, feel and appearance, and can be used in the fields of flake filling and textile fabrics. Polyamide ester fiber fabrics are soft and comfortable, and their comprehensive properties such as anti-pilling, moisture absorption and quick drying are better than those of cotton and polyester. The coloring rate of normal pressure dyeing is high and the color fastness is good; the spinning process of polyamide ester fiber should be relatively gentle, and the dyeing and finishing should choose a reasonable process flow, and control the pH value and temperature of the dye bath. Polyamide ester fiber fabrics have great advantages in wearability in the fields of knitting and weaving. In addition, polyamide ester fiber is softer than polyester fiber and has a cotton-like feel, so it is loved by consumers.

[0003] Although the current technology of heat-retaining heating fibers achieves the purpose of heating fabrics, it easily affects the basic wearing properties of the fabrics, such as strength and heat resistance. Therefore, the present invention studies and prepares a high-strength light-absorbing heating fiber with excellent heat resistance. Summary of the invention

[0004] The purpose of the present invention is to provide a high-strength light-absorbing heat-generating fiber and a preparation method thereof to solve the problems raised in the above-mentioned background technology.

[0005] In order to solve the above technical problems, the present invention provides the following technical solutions: a high-intensity light-absorbing and heat-generating fiber, wherein the high-intensity light-absorbing and heat-generating fiber is obtained by mixing modified polyamide ester with nano-microcapsules and then melt-spinning.

[0006] Preferably, the modified polyamide ester fiber is prepared by melt spinning of modified polyamide ester; the modified polyamide ester is prepared by reacting cross-linked maleic anhydride, diisopropanolamine and trimethylolpropane to form a hyperbranched polyamide ester, which is then reacted with trimesic acid.

[0007] Preferably, the cross-linked maleic anhydride is prepared by the cross-linking reaction of 2-acrylamido-2-methylpropanesulfonic acid, acrylamide and maleic anhydride.

[0008] Preferably, the nano-microcapsules are prepared by coating the surface of nano-powder with mesoporous melamine resin; the nano-powder includes far-infrared ceramic powder and nano-zirconium carbide.

[0009] Preferably, the high-intensity light-absorbing heat-generating fiber and the preparation method thereof include the following specific steps:

[0010] S1. After reflux dehydration of diisopropanolamine for 1-2 hours, add N,N-dimethylacetamide solution of cross-linked maleic anhydride 5-6 times the mass of diisopropanolamine, the mass ratio of cross-linked maleic anhydride to N,N-dimethylacetamide is 1:(5-6), react at room temperature for 3-6 hours, distill under reduced pressure, then add diphenylmethane 6-8 times the mass of diisopropanolamine and trimethylolpropane 0.1-0.2 times the mass of diisopropanolamine, heat to 170-180°C in a nitrogen atmosphere, react for 6-8 hours, and distill under reduced pressure again to obtain hyperbranched polyamide ester;

[0011] S2. The hyperbranched polyamide ester and trimesic acid are mixed in a mass ratio of 3:(1-2), stirred evenly, and then heated to 80-90°C, and concentrated sulfuric acid in an amount of 0.1-0.3 times the mass of the hyperbranched polyamide ester is added dropwise at a rate of 1-3 ml / min, and the reaction is continued for 6-12 hours to obtain a modified polyamide ester;

[0012] S3. Mix polyether F127 as a template, hexadecyltrimethylammonium bromide and deionized water in a mass ratio of (1.5-6): (1-3): (20-30), stir evenly, add 8-10 times the mass of hexadecyltrimethylammonium bromide prepolymer solution and 0.6-0.8 times the mass of hexadecyltrimethylammonium bromide nanopowder suspension, adjust the pH to 2-3 with hydrochloric acid, heat to 70-80°C, react for 30-40 minutes, quickly transfer to a stainless steel reactor, perform hydrothermal treatment at 120-160°C for 12-24 hours, the temperature is 120-160°C, cool to room temperature, crush and rinse with deionized water for 8-10 minutes, grind into powder after drying, wash with ethanol 3-5 times and dry to obtain nano-microcapsules;

[0013] S4. The modified polyamide ester and nano-microcapsules are mixed in a mass ratio of (40-50):1, stirred evenly, and then transferred to a vacuum drying oven at 140-160°C for drying for 24 hours. The slices are fed into the feed hopper of a melt spinning machine and melt-spun to obtain light-absorbing and heat-generating fibers.

[0014] Preferably, in the above step S1., the preparation method of cross-linked maleic anhydride is: 2-acrylamido-2-methylpropanesulfonic acid and deionized water are mixed in a mass ratio of 1:20-30, stirred and dissolved, and then the pH is adjusted to 2-3 with sodium hydroxide, acrylamide, maleic anhydride and N,N-methylenebisacrylamide are added, and then stirred at 400-800 rpm for 24 hours. The mass ratio of 2-acrylamido-2-methylpropanesulfonic acid, acrylamide, maleic anhydride and N,N-methylenebisacrylamide is (1.8-2):1.5:0.3:(0.01-0.02), and cross-linked maleic anhydride is obtained.

[0015] Preferably, in the above step S3., the preparation method of the prepolymer solution is: melamine, deionized water and a formaldehyde solution with a mass fraction of 37-40% are mixed in a mass ratio of 1:1.6:(2-3), the pH is adjusted to 8.2-8.5 with sodium hydroxide, the temperature is raised to 80-82°C and refluxed for reaction for 30-40 minutes, and then sodium bisulfite with a mass of 0.7-0.8 times that of melamine is added, and the reaction is continued for 1-3 hours to obtain a prepolymer solution.

[0016] Preferably, the preparation method of the nano powder suspension is: mixing the nano powder, deionized water and styrene-maleic anhydride copolymer sodium salt in a mass ratio of (3-7):100:10, stirring evenly, and preparing the nano powder suspension.

[0017] Preferably, the nano powder includes far-infrared ceramic powder and nano zirconium carbide, and the mass ratio of the far-infrared ceramic powder to the nano zirconium carbide is 3:(1-2).

[0018] Preferably, in the above step S4., during melt spinning, the temperature of spinning zone I is 280~282°C, the temperature of spinning zone II is 290~292°C, the temperature of spinning zone III is 288~290°C, the temperature of spinning zone IV is 286~288°C, the temperature of spinning metering pump zone is 284~286°C, the temperature of spinning elbow tube zone is 284~286°C, the temperature of spinning box zone is 286~288°C, the traction multiple is 3.5~4.5, the temperature of hot roller is set to 80~82°C, and the heat setting temperature is 160~164°C.

[0019] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0020] The high-strength light-absorbing and heat-generating fiber prepared by the present invention is prepared by mixing modified polyamide polyester with nano-microcapsules and then performing melt spinning;

[0021] The modified polyamide ester is prepared by reacting cross-linked maleic anhydride, diisopropanolamine and trimethylolpropane to form a hyperbranched polyamide ester, which is then reacted with trimesic acid. The cross-linked maleic anhydride is prepared by cross-linking 2-acrylamide-2-methylpropanesulfonic acid, acrylamide and maleic anhydride. The cross-linked maleic anhydride with a high cross-linking degree is prepared by cross-linking 2-acrylamide-2-methylpropanesulfonic acid, acrylamide and maleic anhydride, which is then reacted with diisopropanolamine and trimethylolpropane to form a hyperbranched polyamide ester with terminal hydroxyl groups, which is finally reacted with trimesic acid to introduce a large number of benzene rings into the polyamide ester and form a cross-linked structure, thereby enhancing the heat resistance and strength of the modified polyamide ester.

[0022] Nano-microcapsules are prepared by coating mesoporous melamine resin on the surface of nano-powder. The nano-powder includes far-infrared ceramic powder and nano-zirconium carbide. When preparing the mesoporous melamine resin, nano-powder emulsion is introduced, and in-situ polymerization is carried out on the surface of far-infrared ceramic powder and nano-zirconium carbide to form nano-microcapsules, which are introduced into modified polyamide ester fibers. They can absorb light and generate heat while entering into the cross-linked structure, further enhancing the heat resistance and strength of the light-absorbing and heat-generating fibers. DETAILED DESCRIPTION

[0023] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0024] In the present invention, 2-acrylamido-2-methylpropanesulfonic acid was purchased from Hubei Shishun Biotechnology Co., Ltd., far-infrared ceramic powder brand PT-YH68 was purchased from Anhui Shangmeiheng Nanomaterial Co., Ltd., with an average particle size of 100-300 nm, and nano zirconium carbide CAS 12070-14-3 was purchased from Shanghai Yaotian New Material Technology Co., Ltd., with an average particle size of 30-50 nm.

[0025] In order to more clearly illustrate the method provided by the present invention, the following examples are used to describe in detail the various index testing methods of the high-intensity light-absorbing and heat-generating fibers prepared in the examples and comparative examples as follows:

[0026] Mechanical properties: The high-strength light-absorbing and heat-generating fibers prepared in the examples and comparative examples were tested for breaking strength and breaking elongation according to GB / T8960-2015.

[0027] Heat resistance: The high-intensity light-absorbing and heating fibers prepared in the examples and comparative examples were irradiated with 150 W infrared light for 1 hour, cooled naturally, and repeated 100 times, and then the mechanical properties were tested again.

[0028] Example 1

[0029] S1. 2-acrylamide-2-methylpropanesulfonic acid was mixed with deionized water in a mass ratio of 1:20, stirred and dissolved, and then the pH was adjusted to 2 with sodium hydroxide, acrylamide, maleic anhydride and N,N-methylenebisacrylamide were added, and then stirred at 400rpm for 24h. The mass ratio of 2-acrylamide-2-methylpropanesulfonic acid, acrylamide, maleic anhydride and N,N-methylenebisacrylamide was 1.8:1.5:0.3:0.01 to obtain cross-linked maleic anhydride. anhydride; after refluxing and dehydrating diisopropanolamine for 1 hour, add N, N-dimethylacetamide solution of cross-linked maleic anhydride 5 times the mass of diisopropanolamine, the mass ratio of cross-linked maleic anhydride to N, N-dimethylacetamide is 1:5, react at room temperature for 3 hours, distill under reduced pressure, then add diphenylmethane 6 times the mass of diisopropanolamine and trimethylolpropane 0.1 times the mass of diisopropanolamine, heat to 170°C in a nitrogen atmosphere, react for 6 hours, and distill under reduced pressure again to obtain hyperbranched polyamide ester;

[0030] S2. The hyperbranched polyamide ester and trimesic acid were mixed in a mass ratio of 3:1, stirred evenly, and then heated to 80 ° C., concentrated sulfuric acid with a mass of 0.1 times the mass of the hyperbranched polyamide ester was added dropwise at a rate of 1 ml / min, and the reaction was continued for 6 hours to obtain a modified polyamide ester;

[0031] S3. Melamine, deionized water and 37% formaldehyde solution are mixed in a mass ratio of 1:1.6:2, the pH is adjusted to 8.2 with sodium hydroxide, the temperature is raised to 80°C and refluxed for 30 minutes, and then sodium bisulfite in an amount of 0.7 times the mass of melamine is added, and the reaction is continued for 1 hour to obtain a prepolymer solution; nanopowder, deionized water and styrene-maleic anhydride copolymer sodium salt are mixed in a mass ratio of 3:100:10, and stirred evenly to obtain a nanopowder suspension; the nanopowder includes far-infrared ceramic powder and nano-zirconium carbide, and the mass ratio of far-infrared ceramic powder to nano-zirconium carbide is 3:1; Template F127, hexadecyltrimethylammonium bromide and deionized water are mixed in a mass ratio of 1.5:1:20, stirred evenly, and then a prepolymer solution of 8 times the mass of hexadecyltrimethylammonium bromide and a nano powder suspension of 0.6 times the mass of hexadecyltrimethylammonium bromide are added, the pH is adjusted to 2 with hydrochloric acid, the temperature is raised to 70°C, the reaction is carried out for 30 minutes, and the mixture is quickly transferred to a stainless steel reactor for a hydrothermal treatment at 120°C for 12 hours, the temperature is 120°C, the mixture is cooled to room temperature, crushed, rinsed with deionized water for 8 minutes, dried, ground into powder, washed with ethanol 3 times and dried to obtain nano microcapsules;

[0032] S4. The modified polyamide ester and nano-microcapsules are mixed in a mass ratio of 40:1, stirred evenly and then transferred to a vacuum drying oven at 140°C for drying for 24 hours, sliced ​​and fed into the feed hopper of a melt spinning machine for melt spinning. During melt spinning, the temperature of spinning zone I is 280°C, the temperature of spinning zone II is 290°C, the temperature of spinning zone III is 288°C, the temperature of spinning zone IV is 286°C, the temperature of the spinning metering pump zone is 284°C, the temperature of the spinning elbow tube zone is 284°C, the temperature of the spinning box zone is 286°C, the traction multiple is 3.5, the temperature of the hot roller is set to 80°C, and the heat setting temperature is 160°C to obtain a high-strength light-absorbing and heat-generating fiber.

[0033] Example 2

[0034] S1. 2-acrylamido-2-methylpropanesulfonic acid was mixed with deionized water in a mass ratio of 1:25, stirred and dissolved, and then the pH was adjusted to 2.5 with sodium hydroxide, acrylamide, maleic anhydride and N,N-methylenebisacrylamide were added, and then stirred at 600rpm for 24h. The mass ratio of 2-acrylamido-2-methylpropanesulfonic acid, acrylamide, maleic anhydride and N,N-methylenebisacrylamide was 1.9:1.5:0.3:0.015 to obtain cross-linked maleic anhydride. ; After refluxing and dehydrating diisopropanolamine for 1.5 hours, add N, N-dimethylacetamide solution of cross-linked maleic anhydride with a mass ratio of 5.5 times that of diisopropanolamine, and the mass ratio of cross-linked maleic anhydride to N, N-dimethylacetamide is 1:5.5, react at room temperature for 4 hours, and then distill under reduced pressure, then add diphenylmethane with a mass of 7 times that of diisopropanolamine and trimethylolpropane with a mass of 0.14 times that of diisopropanolamine, heat to 175° C. in a nitrogen atmosphere, react for 7 hours, and distill under reduced pressure again to obtain hyperbranched polyamide ester;

[0035] S2. The hyperbranched polyamide ester and trimesic acid were mixed in a mass ratio of 3:1.5, stirred evenly, and then heated to 85 ° C., concentrated sulfuric acid 0.2 times the mass of the hyperbranched polyamide ester was added dropwise at a rate of 2 ml / min, and the reaction was continued for 9h to obtain a modified polyamide ester;

[0036] S3. Melamine, deionized water and 38% formaldehyde solution are mixed in a mass ratio of 1:1.6:2.5, the pH is adjusted to 8.3 with sodium hydroxide, the temperature is raised to 81°C and refluxed for 35 minutes, and then sodium bisulfite is added in an amount of 0.75 times the mass of melamine, and the reaction is continued for 1 to 3 hours to obtain a prepolymer solution; nanopowder, deionized water and styrene-maleic anhydride copolymer sodium salt are mixed in a mass ratio of 5:100:10, and stirred evenly to obtain a nanopowder suspension; the nanopowder includes far-infrared ceramic powder and nano-zirconium carbide, and the mass ratio of far-infrared ceramic powder to nano-zirconium carbide is 3:1 .5; Mix the template F127, hexadecyltrimethylammonium bromide and deionized water in a mass ratio of 4:2:25, stir evenly, add a prepolymer solution of 9 times the mass of hexadecyltrimethylammonium bromide and a nano powder suspension of 0.7 times the mass of hexadecyltrimethylammonium bromide, adjust the pH to 2.5 with hydrochloric acid, heat to 75°C, react for 35 minutes, quickly transfer to a stainless steel reactor, perform a hydrothermal treatment at 140°C for 18 hours, the temperature is 140°C, cool to room temperature, crush and rinse with deionized water for 9 minutes, grind into powder after drying, wash with ethanol 4 times and dry to obtain nano microcapsules;

[0037] S4. The modified polyamide ester and nano-microcapsules are mixed in a mass ratio of 45:1, stirred evenly, and then transferred to a vacuum drying oven at 150°C for drying for 24 hours. The mixture is sliced ​​and fed into the feed hopper of a melt spinning machine for melt spinning. During melt spinning, the temperature of spinning zone I is 280-282°C, the temperature of spinning zone II is 291°C, the temperature of spinning zone III is 289°C, the temperature of spinning zone IV is 287°C, the temperature of the spinning metering pump zone is 285°C, the temperature of the spinning elbow tube zone is 285°C, the temperature of the spinning box zone is 287°C, the traction multiple is 4.0, the temperature of the hot roller is set to 81°C, and the heat setting temperature is 162°C to obtain a high-strength light-absorbing and heat-generating fiber.

[0038] Example 3

[0039] S1. 2-acrylamido-2-methylpropanesulfonic acid was mixed with deionized water in a mass ratio of 1:30, stirred and dissolved, and then the pH was adjusted to 3 with sodium hydroxide, acrylamide, maleic anhydride and N,N-methylenebisacrylamide were added, and then stirred at 800rpm for 24h. The mass ratio of 2-acrylamido-2-methylpropanesulfonic acid, acrylamide, maleic anhydride and N,N-methylenebisacrylamide was 2:1.5:0.3:0.02 to obtain cross-linked maleic acid. anhydride; after refluxing and dehydrating diisopropanolamine for 2 hours, add N, N-dimethylacetamide solution of cross-linked maleic anhydride 6 times the mass of diisopropanolamine, the mass ratio of cross-linked maleic anhydride to N, N-dimethylacetamide is 1:6, react at room temperature for 6 hours, distill under reduced pressure, then add diphenylmethane 8 times the mass of diisopropanolamine and trimethylolpropane 0.2 times the mass of diisopropanolamine, heat to 180°C in a nitrogen atmosphere, react for 8 hours, and distill under reduced pressure again to obtain hyperbranched polyamide ester;

[0040] S2. The hyperbranched polyamide ester and trimesic acid were mixed in a mass ratio of 3:2, stirred evenly, and then heated to 90 ° C., concentrated sulfuric acid 0.3 times the mass of the hyperbranched polyamide ester was added dropwise at a rate of 3 ml / min, and the reaction was continued for 12 hours to obtain a modified polyamide ester;

[0041] S3. Mix melamine, deionized water and 40% formaldehyde solution in a mass ratio of 1:1.6:3, adjust the pH to 8.5 with sodium hydroxide, heat to 82°C and reflux for 40 minutes, then add sodium bisulfite in an amount of 0.8 times the mass of melamine, and continue the reaction for 3 hours to obtain a prepolymer solution; mix nanopowder, deionized water and styrene-maleic anhydride copolymer sodium salt in a mass ratio of 7:100:10, stir evenly, and obtain a nanopowder suspension; the nanopowder includes far-infrared ceramic powder and nano-zirconium carbide, and the mass ratio of far-infrared ceramic powder to nano-zirconium carbide is 3:2; The plate agent F127, hexadecyltrimethylammonium bromide and deionized water are mixed in a mass ratio of 6:3:30, stirred evenly, and then a prepolymer solution of 8 to 10 times the mass of hexadecyltrimethylammonium bromide and a nano powder suspension of 0.8 times the mass of hexadecyltrimethylammonium bromide are added, the pH is adjusted to 3 with hydrochloric acid, the temperature is raised to 80°C, the reaction is carried out for 40 minutes, and the mixture is quickly transferred to a stainless steel reactor for a hydrothermal treatment at 160°C for 24 hours, the temperature is 160°C, the mixture is cooled to room temperature, crushed, rinsed with deionized water for 10 minutes, dried, ground into powder, washed with ethanol 5 times and dried to obtain nano microcapsules;

[0042] S4. The modified polyamide ester and nano-microcapsules are mixed in a mass ratio of 50:1, stirred evenly, and then transferred to a vacuum drying oven at 140-160°C for drying for 24 hours. The mixture is sliced ​​and fed into the feed hopper of a melt spinning machine for melt spinning. During melt spinning, the temperature of spinning zone I is 282°C, the temperature of spinning zone II is 292°C, the temperature of spinning zone III is 290°C, the temperature of spinning zone IV is 288°C, the temperature of the spinning metering pump zone is 286°C, the temperature of the spinning elbow tube zone is 286°C, the temperature of the spinning box zone is 288°C, the traction multiple is 4.5, the temperature of the hot roller is set to 82°C, and the heat setting temperature is 164°C to obtain a high-strength light-absorbing and heat-generating fiber.

[0043] Comparative Example 1

[0044] The composition of comparative example 1 is the same as that of example 2. The difference between the preparation method of the high-strength light-absorbing heat-generating fiber and that of example 2 is that the modified polyamide ester is prepared by reacting maleic anhydride, diisopropanolamine and trimethylolpropane to form a hyperbranched polyamide ester, which is then reacted with trimesic acid.

[0045] Comparative Example 2

[0046] The composition of comparative example 2 is the same as that of example 2. The difference between the preparation method of the high-strength light-absorbing and heat-generating fiber and example 2 is that only the modified polyamide ester is prepared by cross-linking maleic anhydride, diisopropanolamine and trimethylolpropane.

[0047] Comparative Example 3

[0048] The composition of comparative example 3 is the same as that of example 2. The difference between the preparation method of the high-intensity light-absorbing heat-generating fiber and that of example 2 is that the high-intensity light-absorbing heat-generating fiber is prepared by mixing modified polyamide ester with nano powder and then melt-spinning.

[0049] Effect example

[0050] Table 1 below shows the performance analysis results of the high-strength light-absorbing and heat-generating fibers prepared using Examples 1 to 3 of the present invention and Comparative Examples 1 to 3:

[0051] Table 1

[0052] Breaking strength (cN / dtex) Elongation at break (%) Breaking strength after irradiation (cN / dtex) Elongation at break after irradiation (%) Example 1 3.0 26.7 3.0 26.7 Example 2 3.2 27.1 3.2 27.0 Example 3 3.0 26.9 3.0 26.6 Comparative Example 1 2.6 25.4 2.5 25.1 Comparative Example 2 2.5 24.8 2.5 24.3 Comparative Example 3 2.6 24.5 2.4 24.0

[0053] By comparing the experimental data of the embodiments and the comparative examples in Table 1, it can be clearly found that the high-strength light-absorbing and heat-generating fibers prepared using Examples 1, 2, and 3 have excellent mechanical properties and heat resistance.

[0054] From the comparison of the experimental data of Example 1, Example 2, Example 3 and Comparative Example 1, Comparative Example 2, it can be found that the cross-linked maleic anhydride prepared by the cross-linking reaction of 2-acrylamido-2-methylpropanesulfonic acid, acrylamide and maleic anhydride, reacts with diisopropanolamine and trimethylolpropane to form a hyperbranched polyamide ester, and then reacts with trimesic acid to prepare a modified polyamide ester fiber, which has a high degree of cross-linking, introduces a large number of benzene rings into the polyamide ester and forms a cross-linked structure, thereby enhancing the heat resistance and strength of the modified polyamide ester.

[0055] From the comparison of the experimental data of Example 1, Example 2, Example 3 and Comparative Example 3, it can be found that the nano-microcapsules made by coating the mesoporous melamine resin on the surface of the nano-powder are introduced into the modified polyamide ester, the mesoporous melamine resin, the nano-powder emulsion is introduced, and in situ polymerized on the surface of the far-infrared ceramic powder and nano-zirconium carbide to form nano-microcapsules, which are introduced into the modified polyamide ester fiber, can absorb light and generate heat while entering into the cross-linked structure, further enhancing the heat resistance and strength of the light-absorbing and heat-generating fiber.

[0056] Obviously, the above embodiments are merely examples for clearly illustrating the embodiments of the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. However, these obvious changes or modifications derived from the spirit of the present invention are still within the scope of protection of the present invention.

Claims

1. A light-absorbing heat-generating fiber, characterized in that: The light-absorbing heat-generating fiber is prepared by mixing modified polyamide ester with nano-microcapsules and then performing melt spinning; the modified polyamide ester is prepared by reacting cross-linked maleic anhydride, diisopropanolamine and trimethylolpropane to form hyperbranched polyamide ester, and then reacting with trimesic acid; the nano-microcapsules are prepared by coating the surface of nano-powder with mesoporous melamine resin; the nano-powder includes far-infrared ceramic powder and nano-zirconium carbide; the preparation method of the cross-linked maleic anhydride is as follows: 2-acrylamide-2-methylpropanesulfonic acid The mixture was mixed with deionized water at a mass ratio of 1:20-30, stirred and dissolved, and then the pH was adjusted to 2-3 with sodium hydroxide. Acrylamide, maleic anhydride and N,N-methylenebisacrylamide were added, and then stirred at 400-800 rpm for 24 hours. The mass ratio of 2-acrylamido-2-methylpropanesulfonic acid, acrylamide, maleic anhydride and N,N-methylenebisacrylamide was (1.8-2):1.5:0.3:(0.01-0.02), and cross-linked maleic anhydride was obtained.

2. The light-absorbing heat-generating fiber according to claim 1, characterized in that: The mass ratio of the modified polyamide ester to the nano-microcapsules is (40-50):

1.

3. A method for preparing a light-absorbing heat-generating fiber as claimed in claim 1, characterized in that: The specific steps include: S1. After reflux dehydration of diisopropanolamine for 1 to 2 hours, add N, N-dimethylacetamide solution of cross-linked maleic anhydride 5 to 6 times the mass of diisopropanolamine, the mass ratio of cross-linked maleic anhydride to N, N-dimethylacetamide is 1: (5 to 6), react at room temperature for 3 to 6 hours, distill under reduced pressure, then add xylene 6 to 8 times the mass of diisopropanolamine and trimethylolpropane 0.1 to 0.2 times the mass of diisopropanolamine, heat to 170 to 180 ° C in a nitrogen atmosphere, react for 6 to 8 hours, and distill under reduced pressure again to obtain hyperbranched polyamide ester; S2. The hyperbranched polyamide ester and trimesic acid were mixed in a mass ratio of 3: (1 to 2), stirred evenly, and then heated to 80 to 90 ° C., concentrated sulfuric acid in an amount of 0.1 to 0.3 times the mass of the hyperbranched polyamide ester was added dropwise at a rate of 1 to 3 ml / min, and the reaction was continued for 6 to 12 hours to obtain a modified polyamide ester; S3. The polyether F127 as a template, hexadecyltrimethylammonium bromide and deionized water are mixed in a mass ratio of (1.5-6):(1-3):(20-30), stirred evenly, 8-10 times the mass of hexadecyltrimethylammonium bromide prepolymer solution and 0.6-0.8 times the mass of hexadecyltrimethylammonium bromide nanopowder suspension are added, the pH is adjusted to 2-3 with hydrochloric acid, the temperature is raised to 70-80°C, the reaction is carried out for 30-40 minutes, and the reaction is quickly transferred to a stainless steel reactor for 12-24 hours and 120-160°C hydrothermal treatment, cooled to room temperature, crushed and rinsed with deionized water for 8-10 minutes, dried and ground into powder, and then washed with ethanol 3-5 times and dried to obtain nano-microcapsules; S4. The modified polyamide ester and nano-microcapsules are mixed in a mass ratio of (40-50):1, stirred evenly and then transferred to a vacuum drying oven at 140-160°C for drying for 24 hours, sliced ​​and fed into the feed hopper of a melt spinning machine, melt-spinned to obtain light-absorbing and heat-generating fibers.

4. The method for preparing a light-absorbing heat-generating fiber according to claim 3, characterized in that: In the above step S3., the preparation method of the prepolymer solution is: melamine, deionized water and a formaldehyde solution with a mass fraction of 37-40% are mixed in a mass ratio of 1:1.6:(2-3), the pH is adjusted to 8.2-8.5 with sodium hydroxide, the temperature is raised to 80-82°C and refluxed for reaction for 30-40 minutes, and then 0.7-0.8 times the mass of melamine sodium bisulfite is added, and the reaction is continued for 1-3 hours to obtain a prepolymer solution.

5. The method for preparing a light-absorbing heat-generating fiber according to claim 3, characterized in that: In the above step S3., the preparation method of the nano powder suspension is: mixing the nano powder, deionized water and styrene-maleic anhydride copolymer sodium salt in a mass ratio of (3-7):100:10, stirring evenly, and preparing the nano powder suspension.

6. The method for preparing a light-absorbing heat-generating fiber according to claim 5, characterized in that: The nano powder comprises far-infrared ceramic powder and nano zirconium carbide, and the mass ratio of the far-infrared ceramic powder to the nano zirconium carbide is 3:(1-2).

7. The method for preparing a light-absorbing heat-generating fiber according to claim 3, characterized in that: In the above step S4., during melt spinning, the temperature of spinning zone I is 280-282°C, the temperature of spinning zone II is 290-292°C, the temperature of spinning zone III is 288-290°C, the temperature of spinning zone IV is 286-288°C, the temperature of spinning metering pump zone is 284-286°C, the temperature of spinning elbow tube zone is 284-286°C, the temperature of spinning box zone is 286-288°C, the traction multiple is 3.5-4.5, the temperature of hot roller is set to 80-82°C, and the heat setting temperature is 160-164°C.

Citation Information

Patent Citations

  • Modified poly-(3-hydroxybutanoic acid ester-3-hydroxyvalerate) and spinning method

    CN101550273A

  • A preparation method of a special antibacterial microcapsule for non-woven fabrics

    CN109722909A